Discrete mathematics using Latin squares - Laywine, Charles F. 1937- (Wiley-interslience series in discrete mathematics and optimization, 1998)
An intuitive and accessible approach to discrete mathematics using Latin squares. In the past two decades, researchers have discovered a range of uses for Latin squares that go beyond standard mathematics. People working in the fields of science, engineering, statistics, and even computer science all stand to benefit from a working knowledge of Latin squares. Discrete Mathematics Using Latin Squares is the only upper-level college textbook/professional reference that fully engages the subject and its many important applications.